2017
DOI: 10.4103/ijem.ijem_398_16
|View full text |Cite
|
Sign up to set email alerts
|

Impact of severity of illness on the function of the hypothalamo-pituitary-gonadal axis in postmenopausal women with acute severe illness: Implications for predicting disease outcome

Abstract: Background:While elevated levels of estradiol were predictive of mortality in critically ill surgical and trauma patients, their ability to predict outcome in nonsurgical patients has not been studied. We aimed to study the determinants of gonadotropin levels in acutely ill postmenopausal women with nonsurgical disease and the impact of changes in the gonadal axis on the outcome of these patients.Methods:Thirty-five postmenopausal women admitted to medical intensive care with acute severe illness and having a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Accordingly, a prospective study, which evaluated sex differences in respiratory physiology and the development of chronic obstructive pulmonary disease (COPD), reported that early menopause was associated with greater risk of COPD-related hospitalization or death [ 14 ]. Meanwhile, E2 in critically ill or injured adults was independently associated with mortality [ 15 , 16 ], and low E2 was a diagnostic feature for prolonged hospital stay in critically ill surgical and trauma patients [ 17 ]. In addition, because menstruation could be affected by factors such as body mass index, drug intake, environment, and emotion [ 18 ], aside from the periodic fluctuation of sex hormones, further study of sex hormones was performed to more objectively evaluate the effect of sex difference.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a prospective study, which evaluated sex differences in respiratory physiology and the development of chronic obstructive pulmonary disease (COPD), reported that early menopause was associated with greater risk of COPD-related hospitalization or death [ 14 ]. Meanwhile, E2 in critically ill or injured adults was independently associated with mortality [ 15 , 16 ], and low E2 was a diagnostic feature for prolonged hospital stay in critically ill surgical and trauma patients [ 17 ]. In addition, because menstruation could be affected by factors such as body mass index, drug intake, environment, and emotion [ 18 ], aside from the periodic fluctuation of sex hormones, further study of sex hormones was performed to more objectively evaluate the effect of sex difference.…”
Section: Discussionmentioning
confidence: 99%